Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen dan Komite Audit Terhadap Penghindaran Pajak (Tax Avoidance) pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2016 - Noor Mita Dewi (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2019)
This study aims to predict empirical evidence regarding the effect of institutional ownership, independent boards and audit committees partially or simultaneously on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016. Based on this, this study takes the title " The Influence of Institutional Ownership, the Independent Board of Commissioners and the Audit Committee on Tax Avoidance in Banking Companies listed on the Indonesia Stock Exchange for the Period 2012 - 2016 ". The selected population of all banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016. The sampling method used in this study is the cluster sampling method, which is a form of purposive sampling by taking a predetermined sample based on the aims and objectives of the study, which obtained 115 samples from banking companies. The data used are secondary data with linear regression data analysis. Based on the research results, it is known that institutional ownership has a positive and significant effect on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016 so that the hypothesis is accepted. The independent board of commissioners has a positive and significant effect on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016 so that the hypothesis is accepted. The audit committee has no significant effect on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016, so the hypothesis is rejected. Institutional ownership, independent board of commissioners and audit committee have a positive and significant effect on tax avoidance in banking companies listed on the Indonesia Stock Exchange for the period 2012 - 2016 so that the hypothesis is accepted.